Beyond the Mantra of ‘Stomach Infrastructure’: Ekiti Politics and the Sociology of Voting in the 2015 Elections - Olaniyan, Azeez (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The uniqueness of the 2015 election in Ekiti State lies not only in the professional conduct of the electoral umpire especially its innovations, which facilitated a free and fair process, and acceptable outcomes, but also in the emergent sociology of voting behaviour exhibited by the people of the state. Results of the elections in Ekiti State, hitherto reputed as the hub of progressive politics the Southwest is known for, constituted a radical departure from the conventional disposition. The APC, in spite of its progressive slogan, was trounced by the PDP in all the elections. Even, the much-anticipated bandwagon effect of the APC success at the presidential poll did not materialise as the PDP won all the National and State Assembly seats. Although this exceptional feat was consistent with the behaviour exhibited in the 2014 gubernatorial election when the PDP defeated the incumbent APC Governor, yet this pattern of voting contradicted previous behaviour in the history of electioneering in the state; for, no single party has ever recorded consistent absolute electoral victory in all general elections conducted in the state. Using primary and secondary data sourced from interviews, personal observations and texts, this paper seeks to interrogate the emergent sociology of voting behaviour in Ekiti State. Meanwhile, the popularity of the catchphrase ‘stomach infrastructure’, seems to overshadow the main issues shaping the outcomes of the elections in the state. This paper engages in a critical examination of the main issues that influenced the voting behavior of Ekiti people in the 2015 general elections.